Study Protocol of Brief Daily Body-Mind-Spirit Practice for Sustainable Emotional Capacity and Work Engagement for Community Mental Health Workers: A Multi-Site Randomized Controlled Trial - Ng, S. M.; Lo, Herman H. M.; Yeung, Albert; Young, Daniel; Fung, Melody H. Y.; Wang, Amenda M. (Frontiers in Psychology, 2020)
Background: In view of the emotional demanding nature of social services, we developed a brief daily body-mind-spirit (BMS) program and successfully piloted it with workers at elderly services. The proposed study focuses on community mental health workers who are often under chronic stress and vulnerable to burnout. Methods: The study aims to evaluate the program for fostering sustainable emotional capacity and work engagement for community mental health workers. A multi-site randomized controlled trial design is adopted. All the 24 the Integrated Community Centre for Mental Wellness (ICCMW) of Hong Kong will be invited to participate in the study. Assuming a conservative response rate of 60%, about 14 ICCMWs will join. At each site, a pair of intervention and control groups will be run. The targeted total sample size is 224. To investigate the course of changes in burnout and engagement, each group will last 6 months, including 3-month intervention and 3-month follow-up. Measures will be taken at monthly intervals. Discussion: Most staff well-being programs are one-off in design, and can hardly produce sustaining effects. The proposed study will demonstrate that a continued well-being program can be feasible and effective. At theoretical level, the study will reveal new understanding of work engagement. Our pilot trials revealed reduction of exceptional high engagement alongside with reduction of burnout. Engagement may be like ‘fire’ fueling us at work, but it can ‘burn’ if it is overly strong. There may be an optimal range for work engagement.